Świadome życie gorszycielki - Szopa, Katarzyna (Śląskie Studia Polonistyczne, 2012)
The book by Agata Zawiszewska, a researcher from Szczecin, fully devoted to the columnist-writing of Irena Krzywicka, a well-known inter-war writer and activist, is a perfect compendium of knowledge about the changes of traditions of the Second Republic of Poland. The author of a thick book concentrates above all on a discontinued Polish feminist thought, and places Krzywicka’s works on a map of female writing. Życie świadome. O nowoczesnej prozie intelektualnej Ireny Krzywickiej is a large-scale project worthy of a feminist conception of ginocriticism, the nature of which is above all the woman, her works, action and life conscious of the inter-war period.